Long‐term Trends in Head and Neck Surgery Outcomes. (10th July 2018) - Mowery, Alia; Light, Tyler; Clayburgh, Daniel
Abstract : Objective: The aim of the present study is to address the paucity of data on long‐term trends in postoperative complication rates in head and neck surgery. Specifically, this study assesses trends in morbidity and mortality following head and neck surgery over a 20‐year period from 1995 to 2015 and identifies risk factors for the development of complications. Study Design: Retrospective cross‐sectional analysis of Veterans Affairs Surgical Quality Improvement Program database from 1995 to 2015. Setting: Veterans Affairs medical centers across the United States. Subjects and Methods: Using the Veterans Affairs Surgical Quality Improvement Program database, we selected 44, 161 patients undergoing head and neck procedures from 1995 to 2015. Trends in 30‐day morbidity and mortality were assessed, and univariate and multivariate analyses of risk factors for complications were performed. Results: From 1995‐2000 to 2011‐2015, overall complication rates decreased >45% (from 10.9% to 5.9%), and 30‐day postsurgical mortality decreased nearly 70% (from 1.3% to 0.4%). Postoperative hospital stays also significantly declined. Major procedures, such as free flap cases and total laryngectomies, had less change in complication rate as compared with less invasive procedures. Conclusion: Substantial improvement in postoperative morbidity and mortality has taken place in head and neck surgery over the past decades. Static complication rates in some procedures may reflect that the improvement of surgical techniques allow for the treatment of sicker patients. The trends seen in this study speak to the importance of probing further why high rates of complications are still seen in certain procedures and ensuring that effective treatment is balanced with limiting morbidity and mortality.